EKSISTENSI PENGRAJIN GERABAH DI KELURAHAN KEDATON KECAMATAN KAYU AGUNG TAHUN 1980-2020 - Adinda Putri Wiryani; Niswatun Hasibah; Vina Anjelina; Syarifuddin Syarifuddin; Supriyanto Supriyanto (Universitas PGRI Palembang, 2022)
[The Existence of Pottery Craftsmen in Kedaton Village Kayu Agung District 1980-2020] This study highlights the problem of how the existence of pottery craftsmen in Kedaton Village, Kayu Agung District in 1980-2020. The method used in this study is a historical sociological approach which aims to provide an explanation of the existence of pottery in Kedaton Village, Kayu Agung District. This discourse will be used as a warning to the community to protect and preserve the existing culture. Data collection techniques in research were carried out by means of observation, interviews and documentation in the field. Sources of data in the study were obtained from sources who work as pottery craftsmen in Kedaton Village who have been working on pottery craft from generation to generation. This research shows that craftsmen of pottery crafts in Kedaton Village, Kayu Agung District still exist. However, there has been a decline in terms of the pottery craftsmen themselves. This is due to several factors, that is: The high cost of pottery raw materialsthe time in pottery making, the age factor, and the change in the livelihood sector which creates difficulties for the craftsmen who are still engaged in making pottery in Kedaton Villager. This article presents changes in the existence of a culture due to the absence of efforts to preserve that culture